Lateral approach for recurrent unilateral cervical radiculopathy after anterior discectomy with fusion. Report of two cases - Artur Balasa; Mateusz Bielecki; Marek Prokopienko; Przemysław Kunert (Videosurgery and Other Miniinvasive Techniques)
Recurrent radiculopathy after anterior cervical discectomy with fusion (ACDF) occurs in approximately 4% of cases. The main obstacles of revision surgery after ACDF via the same approach are scar tissue and arthrodesis. We present two patients with recurrent symptoms after ACDF who underwent revision surgery using an alternative, less invasive lateral approach (LA). These two patients both presented with recurrent unilateral cervical radiculopathy due to progression of intervertebral foraminal stenosis. The second patient also presented with paraparesis of the lower limbs and central stenosis. Anterior foraminotomy in the first case and oblique corpectomy in the second were performed via the LA. The previously implanted interbody cages were left intact and no new fusion procedures were needed. No spinal instability or symptom relapse was observed in follow-up. The lateral approach to the cervical spine enables direct and effective decompression of neural structures without violation of previously achieved interbody fusion.